P01.066 Patients with EGFR amplification but without EGFRvIII expression have improved benefit compared to those with EGFRvIII expression in samples of the INTELLANCE 2/EORTC 1410 randomized phase II trial. (19th September 2018) - French, P J; Kros, J; de Heer, I; Ansell, P; Looman, J; Bain, E; Morfouace, M; Gorlia, T; Golfinopoulos, V; van den Bent, M
Abstract: Background: Depatux-M is an antibody-drug-conjugate consisting of an antibody (ABT-806) bound to the toxin monomethylauristatin-F. A randomized phase II trial on EGFR-amplified recurrent glioblastomas (GBMs) showed a significant improvement (p=0.06 in the primary analysis, p=0.024 in follow-up analysis) in overall survival in the Depatux-M+TMZ arm when compared to the control arm (CCNU or TMZ). In this study, we performed targeted next generation sequencing and correlated molecular features with response to treatment in order to better identify patients that benefit from the combination. Material and Methods: DNA and RNA was isolated from samples, collected at initial diagnosis, and selected for regions with highest tumor content. Target selection was done using the Trusight 170 gene panel (Illumina) which interrogates somatic variants and copy number, RNA levels and fusion genes in a set of known cancer genes. Variant calling was done using the Illumina Basespace sequence hub. For this trial, patients were eligible with centrally confirmed EGFR amplification, defined as EGFR/CEP 7 (centromere) ratio ≥ 2 in 15% of cells (FISH) Results: DNA and RNA data were generated from 233 and 234 samples respectively (of the 260 study patients). High-copy gene amplification was detected in EGFR (n=202), MDM2 (n=20), MDM4 (n=22), CDK4 (n=24) and CDK6 (n=5) which correlated with high expression levels. With this assay, 17 tumors did not show EGFR copy number (cn) aberrations (cn < 2.8), a further 14 showed copy number changes consistent with trisomy (2.8< cn < 4). Most EGFR amplified tumors also had additional genetic changes in the EGFR locus including point mutations (111/202), splice variants (132/202, the most common being EGFRvIII n=96) or fusion genes (13/202). Twenty-one samples did not contain additional genetic changes and expressed only EGFRwt. Response to treatment was not correlated to EGFR gene expression or amplification levels though, since EGFR amplification was a pre-requisite for inclusion, the majority of cases expressed high levels of EGFR. Preliminary analysis in the Depatux-M +TMZ arm suggests that subjects with EGFR amplification but without EGFRvIII expression had a superior clinical benefit to those with EGFRvIII expression (median survival 14.6 v. 9.2 months, HR 0.57, P=0.04). No such association was identified in the Depatux-M or TMZ/CCNU arms where the median survival of EGFRvIII negative v positive was 7.7 v . 8.3 and 8.8 v . 7.5 months respectively. Conclusion: Depatux-M in combination with TMZ showed a trend towards improved OS in EGFR amplified recurrent glioblastoma. This trend may be greater for subjects with an absence of EGFRvIII expression.